Os efeitos do ensino de tato para itens de alta e baixa preferência na emergência do mando em crianças com autismo - Mendes, Valeria (2013)
Children with atypical development and with verbal behavior deficits, specifically children with autism, can benefit from a systematic teaching of verbal operants and programs that promote its generalization. Verbal behavior is an operant behavior maintained by consequences mediated by a listener that was previously trained by the verbal community to respond to such verbal stimuli. Among the verbal operants, three were of particular interest to this research: echoic, tact and mand. The aim of this research was to examine the effects of tact training for high and low preferred leisure items in the emergence of mand for these same items. Five students with autism (aged from 5 to 14 years old) attending a special education school participated in this research. Participants were exposed one at a time to the experimental conditions and the behavior was observed in the test condition of mand, teaching tact and, then, the effects of the tact teaching was observed in the emergence of mand. The experimental stimuli (leisure items and edibles) were selected from the indication of the parents and teacher, followed by a Forced Choice preference assessment. At the end of the teaching procedure, participants presented tact for high (AP) and low preferred (BP) items. In the mand post-test, participants demonstrated the emergence of this operant with a higher frequency of responses for AP items. The results suggest that the emergence of mands with a higher frequency of responses for AP items may be related to the motivating operation, since the AP items could exert a more reinforcing function than the BP items, which has practical implications for the teaching of verbal behavior.